Praktik Gadai dalam Masyarakat Minangkabau: Analisis Wacana Van Dijk atas Surat Pagang Gadai Koleksi British Library Kode EAP 144/3/67 dan 144/3/82 - Anisa Nurul Azkiya; Priscila Fitriasih Limbong (Gurindam: Jurnal Bahasa dan Sastra, 2025)
This research aims to reveal three levels of discourse in the pawnshop letters of the British Library collection number EAP 144/3 codes EAP144/3/67 and EAP144/3/82. The methods used are the philological and descriptive-analytical methods. In addition, Teun A. van Dijk's Critical Discourse Analysis (AWK) approach was used to look at macro, micro, and superstructure discourses. The results show that the word choice and structure of the two letters reflect the form of economic relations and power relations in Minangkabau society.